Birds of a feather flock (even more) together: An intergroup relations perspective on how # MeToo ‐related media coverage affects the evaluation of prospective corporate directors - Bednar, Michael K.; Westphal, James D.; McDonald, Michael L. (Strategic Management Journal, 2022)
Abstract Research Summary This study examines how incumbent director reactions to media coverage of the #MeToo movement have impacted the evaluation of prospective corporate directors. We argue that heightened intergroup anxiety related to male–female interactions leads incumbents to seize on social attributes that bolster category‐based trust in the reliability of prospective directors' interpersonal behavior. We predict that in response to #MeToo coverage, incumbents evaluate board candidates more positively when they share demographic characteristics or have prior social connections, and these effects are strengthened when incumbents socially identify with the firm. Empirical analyses using a longitudinal survey of evaluations of director candidates support these predictions. Our findings suggest how social movements can produce unintended consequences by inadvertently triggering psychological processes that partially offset the anticipated benefits of the movement. Managerial Summary Increased coverage of #MeToo has heightened concerns among board members about male–female interactions on the board. Our study finds that as #MeToo coverage increases, incumbent directors evaluate potential board candidates more positively to the extent that they share demographic characteristics, including gender, race, functional background, education and age, or when they are connected through the social network of board appointments. These effects are especially pronounced for incumbents who psychologically identify with the firm, meaning that their self‐concept is aligned with features of the organization. Our study suggests how psychological reactions of corporate directors to #MeToo may inadvertently reduce board diversity and overall board effectiveness, and we call for research‐based interventions to correct this unfortunate side effect of a critically important social justice movement.